Intraoperative EMG-Based Prediction of Pyramidal Tract Side Effects During Deep Brain Stimulation for Essential Tremor Under General Anesthesia - Ninan, Melvin K.; Kommula, Lakshman R.; Ginjupally, Dhanunjaya R.; Rajabhushanam, Moparthi (Journal of Neuroanaesthesiology and Critical Care, 2025)
Deep brain stimulation (DBS) for essential tremor (ET) poses challenges for both neurosurgeons and neuroanesthetists. ET with prominent postural and action tremors may respond better to DBS targeting the caudal zona incerta (cZI) than the traditional ventral intermediate nucleus. A key intraoperative concern is identifying the pyramidal tract side effect (PTSE) threshold, as a low threshold limits the therapeutic window.During awake DBS, macrostimulation helps assess benefits and side effects, including PTSE. Under general anesthesia (GA), however, patient feedback is unavailable. In such cases, intraoperative electromyography (EMG) can detect PTSE responses.We report a case of medication-refractory ET, treated with cZI-targeted DBS under GA. EMG monitoring successfully detected stimulation-induced PTSE, allowing estimation of the threshold without patient input. This highlights the value of EMG in asleep DBS for optimizing lead placement and minimizing side effects when awake testing is not possible.
Keywords: essential tremor; DBS under general anesthesia; caudal zona incerta (cZI); pyramidal tract side effects